2015
DOI: 10.3109/17435390.2014.991429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nano-TiO2on antibiotic resistance transfer mediated by RP4 plasmid

Abstract: The potential risks of nano-materials and the spread of antibiotic resistance genes (ARGs) have become two major global public concerns. Studies have confirmed that nano-alumina can promote the spread of ARGs mediated by plasmids. Nano-titanium dioxide (TiO(2)), an excellent photocatalytic nano-material, has been widely used and is often present in aqueous environments. At various nano-material concentrations, bacterial density, matting time, and matting temperature, nano-TiO(2) can significantly promote the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 45 publications
2
62
0
Order By: Relevance
“…Our previous studies indicated that there is a risk of nanomaterials leading to the development of bacteria resistant to antibiotics. We confirmed that the horizontal transfer of intracellular antibiotic resistance genes (ARGs) occurred via conjugation that was stimulated between two bacteria of same and different genera (Escherichia coli and Salmonella) by the addition of nanoalumina or nano titanium dioxide (Qiu, et al, 2012;Qiu, et al, 2015). In addition, other chemicals or physical methods, such as ionic liquids, ultraviolet exposure and chlorination, could promote ARGs in mobile elements to undergo conjugative transfer between bacteria Luo et al 2014;Guo et al 2015).…”
Section: Introductionsupporting
confidence: 83%
“…Our previous studies indicated that there is a risk of nanomaterials leading to the development of bacteria resistant to antibiotics. We confirmed that the horizontal transfer of intracellular antibiotic resistance genes (ARGs) occurred via conjugation that was stimulated between two bacteria of same and different genera (Escherichia coli and Salmonella) by the addition of nanoalumina or nano titanium dioxide (Qiu, et al, 2012;Qiu, et al, 2015). In addition, other chemicals or physical methods, such as ionic liquids, ultraviolet exposure and chlorination, could promote ARGs in mobile elements to undergo conjugative transfer between bacteria Luo et al 2014;Guo et al 2015).…”
Section: Introductionsupporting
confidence: 83%
“…In addition, it has been demonstrated that ARGs can transfer between organisms in water environments [35]. More importantly, some reports have shown that many kinds of contaminants in water, such as antibiotics, metals and nanomaterials, can promote the transmission of ARGs [36,37]. Even wastewater treatment processes and drinking water chlorination could significantly affect the efficiency of ARG transfer [38].…”
Section: Discussionmentioning
confidence: 99%
“…Q‐PCR was used to quantify the cat gene (chloramphenicol‐resistant gene) carried by donors (Calhoun & Swartz, ), the typical traG gene on the RP4 plasmid carried by both cultivable and uncultivable bacteria (Qiu et al., ), and the mRNA expression level of regulatory genes ( trbBp and trfAp ) involved in RP4‐mediated conjugal transfer using the absolute quantification method. 16S rRNA was used as the internal standard gene, which indicated presence of both cultivable and uncultivable bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…The procedures of RNA extraction and reverse transcription were performed as described by the manufacturers. Finally, the mRNA expression level of the mating pair formation (Mpf) gene, trbBp and the DNA transfer and replication (Dtr) gene, trfAp , were quantified using corresponding primer pairs (Qiu et al., , ).…”
Section: Methodsmentioning
confidence: 99%